PENGARUH DUNIA USAHA TERHADAP PERTUMBUHAN EKONOMI DI KOTA PAREPARE - Hatta, Muhammad; Suriati, Suriati (Cateris Paribus Journal, 2022)
Economic growth is a country's economic problem in the long term. Economic growth measures the achievement of the development of an economy from one period to the next period. This study aims to determine the effect of MSMEs and large businesses on economic growth in Parepare City. This research method is a quantitative descriptive study that uses secondary data in the form of a time series of economic growth in Parepare City for 2014-2019 preriod and the number of MSMEs (Micro, Small and Medium Enterprises) and the number of large businesses in Parepare City for 2014-2019 period. The analytical technique used in this research is multiple linear regression analysis using the SPSS 21 application. Large businesses have a positive and significant effect on economic growth in the Parepare City.